1997
DOI: 10.1002/j.2168-9830.1997.tb00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Perceptions of Academe's Evaluation System

Abstract: This study examined faculty views of the academe's reward system. The study sought to investigate faculty perceptions of the current evaluation system and “how it should be.” Five hundred six engineering faculty at seven universities responded to a questionnaire regarding the methods used to evaluate teaching, the amount of emphasis placed on research, service and teaching and the flexibility of the present system. The results indicate that faculty perceive discrepancies between the current system and what the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…As might be expected, engineering education studies exhibited a strong preference for assigning priority to quantitative data and analysis. For example, it was quite common to develop an extensive control group or pre-test/post-test quantitative design to assess learning and augment it with one or a few open-ended questions to students about their attitude toward the intervention (Campbell et al, 2002;Lee, Castella, and Middleton, 1997;Morell et al, 2001;Raju and Sankar, 1999;Weisner and Lan, 2004). The extent to which authors presented the qualitative results ranges from referencing another publication (Brown, Morning, and Creswell and Plano Clark (2007).…”
Section: B Embedded Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…As might be expected, engineering education studies exhibited a strong preference for assigning priority to quantitative data and analysis. For example, it was quite common to develop an extensive control group or pre-test/post-test quantitative design to assess learning and augment it with one or a few open-ended questions to students about their attitude toward the intervention (Campbell et al, 2002;Lee, Castella, and Middleton, 1997;Morell et al, 2001;Raju and Sankar, 1999;Weisner and Lan, 2004). The extent to which authors presented the qualitative results ranges from referencing another publication (Brown, Morning, and Creswell and Plano Clark (2007).…”
Section: B Embedded Designsmentioning
confidence: 99%
“…Watkins, 2005) to nearly a full page (Morell et al, 2001;Raju and Sankar, 1999). Most included one or two paragraphs discussing student attitudes and intervention logistics (Campbell et al, 2002;Lee et al, 1997;Weisner and Lan, 2004).…”
Section: B Embedded Designsmentioning
confidence: 99%
“…The other common Faculty topic dealt with the cultural and institutional attitude towards engineering education scholarly activities. In 1997, Lee, Castella, et al reported that an extensive survey identified a discrepancy between the current academic reward system and faculty's preference for a flexible system rewarding research, teaching and service activities [16]. Other papers reported on tenure, balancing research and teaching activities, the effect of industrial experience on teaching, and the availability of professional development resources.…”
Section: Results-partmentioning
confidence: 99%
“…This finding is consistent with current literature that describes the university rewards structure for research universities as heavily weighted on research productivity, especially in schools of engineering. [31][32][33][34] The tenure and promotion barrier largely excludes the participation of non-tenured faculty in industrial outreach, and limits participation by tenured associate professors.…”
Section: Barriers To Faculty Participation In Industrial Outreachmentioning
confidence: 99%